Uso sustentado e processamento de llex paraguariensis St. Hill (Erva-Mate) - Valduga, Alice Teresa (Universidade Federal de São Carlos, 2002)
The general objective of this thesis was to study the processing of maté Ilex paraguariensis St. Hil Lineage Cambona 4, a renewable natural resource of sustainable form of small farmers in the South of Brazil. An analysis becomes on the conception of the agricultural producers of the city of Machadinho-RS on environment and maté organic culture. A study of the mate processing is carried out initiating with the singeing, using units of laboratory, which consists one of the conventional stages in the maté processing. The contact time is determined to produce similar leaves to the ones of industrial processes. The best operational condition consisted of singeing per 5 minutes, operating the singer in the rotation of 80 rpm. The initial moisture content of maté leaves varied of 61,9 - 65.0% (db), and to the ending of singeing, under action of combustion gases GLP in the average temperature of 181oC, the moisture content it is reduced for 14,6% (db). The drying was carried out in vibrated tray drier, at the operations conditions: air flow in the temperature and velocity of 60oC and 0,64 m/s; amplitude and frequency of vibration, 0.5,10-3 m and 183 m rd/s, being Aù.2/g equal to 1,7; average specific area initial of maté leaves processed was 52,63 cm2/g. The convective coefficients of heat transfer had been quantified, in the operations of singeing and drying, being obtained the average values, 0,316 at 0,606 and 0,097 kJ/m2.min.oC, respectively. The extraction studies of soluble had been carried through the use of two techniques. The first method, agitation and mixing of maté triturated water, was effected at the temperature of 90oC. It was quantified that 50.7% of solids in the maté dehydrated are constituted by soluble, that were extracted in multiple stages of leaching. In only stage 37.1% of solids are extracted. The second method, with fixed bed of triturated maté, it was used an extractor with perforated chamber for draining of the extract. The experiments had been carried out with multiple extractions, each one with new amount of solvent. In only extraction, 35.5% of solids are extracted. The extract presented a solid concentration of 3,4 to 4,5%. Arabic gum was added to the extract in the concentrations of 0, 0,2; 0,4; 0,6; 0,8; 1,0; 1,5 and 2.0%, in relation to it solids content. The mixtures had been affected with the objective to study the influence of the Arabic gum in the drying and the flavor of drinks. The extracts had been processed in spray dryer at the average operations conditions: temperature and flow air: 190oC and 32.1 m3/h; extract feed at 340 mL/h. The moisture content of powder had varied from 1,8 to 6,6% (db). Sensorial analysis was carried out with three formulations at the concentrations: 0; 0,2 and 1,0% of Arabic gum. To the experimental results a statistical treatment was applied and was verified best preference for the formulations with 0.2% of the Arabian gum content. This showed the influence of the encapsulating agent in the aroma retention. The Arabian gum facilitated the powder separation in the cyclone. Concentrated of soluble of maté they were lyophylisated and obtained the lyophilisation curve. A study of caffeine traced was carried out during the processing. The caffeine determinations were effectuate in the: natura mate; singed maté; dried maté after the singeing and powder maté obtained by spray dryer. The losses of caffeine had been of: 33,6% in singeing 40,7% after the drying in vibrated tray; 62,2% after the spray drying. With soluble extracts of maté of spray drying and lyophilisation new products were developed: Mateccino mate mixing with chocolate ; maté candy and suggestions of fine drinks with maté extract. The economic feasibility study of a plant with capacity for processing 1,500 kg maté leaves/h, it showed: the necessity of: annual fixed capital investment of R$ 390.514,00; that the total annual product cost is of R$ 800.322,00; that the total income is of R$ 1512,000.00 and that the annual profit before taxes is of R$ 711.678,00.
Keywords: Processamento; Erva-mate; Recurso natural renovável; Sapeco; Secagem; Transferência de calor; Extração; Viabilidade econômica; Processing; Maté; Renewable natural resource; Singeing; Drying; Heat transfer; Extraction; Economic feasibility; CIENCIAS BIOLOGICAS